COMPARATIVE ANALYSIS OF SOCIAL MARKETING CAMPAIGN EFFECTIVENESS IN SOCIAL MEDIA BETWEEN MILLENNIAL AND GENERATION Z (CASE STUDY OF â€œDISIPLIN 3Mâ€ COVID-19 PREVENTION CAMPAIGN) - Mongilala, Dave; Saerang, David P. E.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2021)
In December 2019, in Wuhan, China, a new virus named SARS-CoV-2 was found and created a disease later we know as COVID-19 diseases. This virus created a pandemic around the world included Indonesia. To change people's behavior and also aims to raise awareness of how dangerous the COVID-19 is, the Indonesian government released a campaign called â€œDisiplin 3Mâ€ to help to decrease or stop the transmittal cases of the COVID-19. In marketing, this study is known as Social Marketing where the output is to make people change their behavior following the stated output of the advertised campaign. The purpose of this study aims to discover if there significant differences in Social Marketing Campaign Effectiveness between Millennial and Generation Z on Social Media for the case of the â€œDisiplin 3Mâ€ Campaign, especially in Manado city. This research is quantitative research that uses the AIDA Model (Attention, Interest, Desire, and Action) as the measurement of the effectiveness of the advertised campaign. While to know about the differences between the two generation behaviors towards the campaign, this research uses Mann Whitney U-Test as the analytical tool. The result shows that there is a significant difference where Generation Z has bigger means than the Millennial generation towards the Social Marketing Campaign Effectiveness. To maximize the effectiveness of the campaign, the social marketer should know who their target audiences are and their characteristics to provide good content that carries a good and clear message for the audiences to be easily adapted correctly.Â Keywords: social marketing, campaign effectiveness, AIDA, covid-19, millennial, generation z.